Pelatihan Fisika Aeromodelling untuk Siswa SMA Negeri 1 Mataram - Zuhdi, Muhammad; Makhrus, Muh; Wahyudi, Wahyudi; 'Ardhuha, Jannatin; Susilawati, Susilawati; Raharjo, Pranowo (Jurnal Pengabdian Masyarakat Sains Indonesia (Indonesian Journal Of Science Community Services), 2021)
Abstract: One of the materials taught in high school physics learning is fluid dynamics which includes an understanding of aircraft lift which in practice is the basics of aeromodelling. In general, students experience problems in learning, this is due to the lack of practical aspects that are displayed in aeromodelling physics learning. Aeromodeling physics is still considered as something that is difficult and difficult to apply in learning and makes students feel less confident in learning. Most students think that the physics of aeromodelling is difficult and they don't have the ability to build a model of an airplanes. The purpose of this service activity is to train students of SMA Negeri 1 Mataram in understanding the physics of Aeromodelling and applying it in the design and manufacture of aircraft model using the principles of physics. The results show that the students of SMA Negeri 1 Mataram have the ability to understand, apply, and make model airplanes.